Development of diesel-oxygenated blends and exhaust gas recirculation impact on diesel engine’s performance and emission - J. Talib, Lina; M. Salih, Adel (Eastern-European Journal of Enterprise Technologies, 2022)
Most research studies have focused on reducing NOx emitted from diesel engines by adding oxygenated fuels (such as alcohol and biodiesel) to diesel to prepare a good alternative to conventional diesel fuels. Biofuels produced from vegetable oil and waste cooking oil while alcohol can be produced from sugarcane and corn. In the current study, the biodiesel used in the tests was derived from waste cooking oil. In this study, the influence of adding Exhaust Gas Recirculation (EGR) to diesel, biodiesel (D80B20), diesel-pentanol (D85PEN15), diesel octanol (D90OCT10), diesel-propanol (D95PRO5) and diesel-biodiesel-pentanol (D50B40PEN10) blends on performance and emitted pollutants of a diesel engine was investigated. The practical experiments were divided into two parts, the first section comparing the results of using diesel and other fuels at different speeds 2100, 2400, 2700 and 3000 rpm at constant loads without EGR. The second section studied the effect of adding EGR in variable proportions (5 %, 10 %, 15 % and 20 %) to the studied fuel mixtures at constant loads and speed. The results showed that adding biodiesel to diesel (without EGR) increases brake specific fuel consumption, NOx and CO2 emissions by 13.66 %, 41.35 % and 30.49 %, respectively, but, the thermal efficiency of the brakes, exhaust gas temperatures, UHC and CO decreases at rates of 12.58 %, 10.22 %, 18.9 % and 21.31 %, respectively, compared to diesel. When EGR was added at 20 %, the maximum increase for D80B20, D95PRO5, ED100, and D85PENT15 was: 18.38 %, 24.60 %, 45.84 %, and 20 %, respectively, compared to when no EGR was added. The thermal efficiency, exhaust gases temperature and NOx levels decreased when EGR rate was raised